Hybridization of Aminoadamantanes with Cinnamic Acid Analogues and Elucidation of Their Antioxidant Profile - Maya Chochkova; Almira Georgieva; Tsvetelina Ilieva; Madlena Andreeva; Georgi Pramatarov; Nejc Petek; Petranka Petrova; Martin Štícha; Yavor Mitrev; Jurij Svete (Journal of Chemistry)
A series of seventeen cinnamic acid hybrids (4ai–ci) were obtained through an amidation of aminoadamantanes (amantadine, rimantadine, and memantine) with mixed anhydride generated from different substituted cinnamic acid and ethyl chloroformate. 1H NMR, 13C NMR, IR, and HRMS were used for the confirmation of the structures of the synthesized hybrids. Moreover, the antioxidant profiles of amides were estimated as per five different in vitro methods: 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azinobis-3-ethylbenzothiazoline-6-sulfonic acid cation radical (ABTS⁺), ferric reducing antioxidant power (FRAP), cupric reducing antioxidant capacity (CUPRAC) assay, and inhibition of Fe(III)/asc induced lipid peroxidation (LP) in brain homogenate. For comparison, caffeic acid (CaffA), known as a potent naturally occurring antioxidant, was used as a reference compound in our study. The results revealed that the most prominent antioxidant activity was demonstrated by compound 4b2, with excellent CUPRAC, FRAP, scavenging ABTS+˙ potential, and inhibition of Fe/asc–induced LP, followed by 4c6 > 4a6 > CaffA > 4c5 and 4a5 > 4a7. Overall, the results suggest that the hybrids (4b2, 4c6, and 4a6) consisting of a caffeoyl moiety and lipophilic adamantane core endow the molecules with the higher antioxidant activity than their parent compound (caffeic acid), especially against LP. Thus, these promising antioxidants could have beneficial effects in various pathological conditions, where oxidative stress is implicated.